2015
DOI: 10.5694/mja14.01724
|View full text |Cite
|
Sign up to set email alerts
|

Actual availability of general practice appointments for mildly ill children

Abstract: Objective: To determine actual availability and cost of general practitioner appointments for children with conditions of low acuity and low urgency, from the perspective of the child's family. Design, participants and setting: A “secret shopper” method, whereby research assistants posing as parents seeking appointments for mildly ill children telephoned a random sample of 225 general practice clinics within three Melbourne Medicare Local catchments, which included urban, suburban and regional areas; the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In the Australian state of Victoria, the group with the greatest number of emergency department presentations annually is children aged 0 to 4 years . There is evidence that many paediatric emergency department presentations could be safely managed in primary care settings, and much discussion surrounds the need for strategies to encourage parents to use alternatives for urgent care when appropriate …”
mentioning
confidence: 99%
“…In the Australian state of Victoria, the group with the greatest number of emergency department presentations annually is children aged 0 to 4 years . There is evidence that many paediatric emergency department presentations could be safely managed in primary care settings, and much discussion surrounds the need for strategies to encourage parents to use alternatives for urgent care when appropriate …”
mentioning
confidence: 99%
“…comm., 2014). Recent studies have suggested that it is neither a lack of primary care availability, nor the time of day (or night) that drives patients to come to the ED – however this remains a focus of national health policy.…”
mentioning
confidence: 99%
“…Many of these parents believed no appointments would be available. However, a recent study has demonstrated broad same‐day GP appointment availability for children with lower urgency conditions in the same catchment areas as our study hospitals . Further, most of those same GP practices bulk‐bill, suggesting that cost is unlikely to be a significant barrier in accessing such services.…”
Section: Discussionmentioning
confidence: 65%